TINGKAT INTENSITAS PERTEMUAN PEMBELAJARAN SISWA DI SMP NEGERI 2 AIKMEL - Agus Fahmi (Jurnal Paedagogy, 2017)
n an educational institution, learning achievement is an important indicator to measure the success of the teaching and learning process. However, it cannot be denied that the high and low level of student achievement is influenced by other factors besides the teaching process itself, namely the intensity of learning meetings. This study aims to determine the level of intensity of learning meetings with student achievement at SMPN 2 Aikmel, East Lombok Regency. The subjects in this study were the principal and teachers. The research approach used in this research is a qualitative approach using a case study design. The method of data collection was carried out by in-depth interviews with informants and data collection of supporting documents about teacher and principal learning meetings. Data analysis consists of three activities that occur simultaneously, namely: data reduction, data presentation, drawing conclusions / verification. The results of this study indicate the intensity of the learning meeting at SMPN 2 Aikmel, East Lombok, when viewed from each indicator, it shows that the attendance rate is in the very high category, the administrative and regulatory discipline is very high, the learning responsibility is in the very high category, the cooperation is in the category. high, and effective study time in the high category.